The Analysis of the Comparison of the Education System in Indonesia: Perspectives on Gaps and Innovation - Rahman, Waskito; Asha, Lukman; Fakhruddin (The Future of Education Journal, 2024)
Education plays a strategic role in developing high-quality human resources, yet Indonesia continues to face significant challenges in addressing educational disparities. This study aims to analyze the comparative aspects of Indonesia’s education systems, including public schools, private schools, Islamic boarding schools (pesantren), and community-based education, with a focus on disparities and innovations. Using a qualitative-descriptive approach, data were collected from literature reviews, government reports, and interviews with education practitioners.The analysis reveals substantial challenges in accessibility, teacher quality, and infrastructure, particularly in remote areas. Public schools, while providing broad access, often face limitations in facilities and educational quality. In contrast, private schools demonstrate higher standards but remain accessible only to certain socioeconomic groups due to cost barriers. Islamic boarding schools offer value-based education but may lack integration with general education standards. Meanwhile, community-based education emerges as a viable solution for remote areas but requires stronger policy support. The study also highlights that innovations such as the Merdeka Belajar program and digital technology adoption can serve as catalysts for reducing educational disparities. The findings underscore the need for more inclusive policies, enhanced teacher capacity, and increased investment in infrastructure to achieve equitable and high-quality education.